Dampak perbedaan suku bunga terhadap permintaan uang: Kasus Amerika Serikat dan Indonesia - Dina Marlina; Sri Andaiyani; Dedi Hartawan (Department of Development Economics, Universitas Sriwijaya, 2018)
This study aims to look at the demand for money in Indonesia 2010Q1-2017Q4. In this research using the VAR (Vector Auto Regressive) model. This study attempts to predict time series variables and on the dynamic impact of analysis of disturbance factors in each variable and assesses the interrelationships between variables using the program Eviews 9.0. In this study, researchers tried to test Frriedman's theory by focusing on the difference between Indonesian interest rates and US interest rates. The important thing is, this study argues that the differential US dollar interest coefficient from the money demand function can describe financial dollarization in Indonesia. Indonesia is trying to keep capital flows out of other countries, especially the United States by keeping interest rates higher than the United States. This means that the higher interest rate differentials between Indonesia and the United States will make more capital inflow to Indonesia, so will make higher demand for money in Indonesia. The results show that all variables used in this study are stationary at first difference and have the appropriate model in lag 5